Diagnóstico ecocardiográfico fetal y posnatal de la ventana aortopulmonar - García Guevara, Carlos; Díaz Ramírez, Francisco; Ramiro Novoa, Juan C. (CorSalud, 2019)
Diagnóstico ecocardiográfico fetal y posnatal de la ventana aortopulmonar